8-Plex Quantitation of changes in cerebrospinal fluid protein expression in subjects undergoing intravenous immunoglobulin treatment for Alzheimer’s disease - Choe, Leila (2007)
An 8-plex version of an isobaric reagent for the quantitation of proteins using shotgun methods is presented. The 8-plex version of the reagent relies on amine-labeling chemistry of peptides similar to 4-plex reagents. MS/MS reporter ions at 113, 114, 115, 116, 117, 118, 119, and 121 m/z are used to quantify protein expression. This technology which was first applied to a test mixture consisting of 8 proteins and resulted in accurate quantitation, has the potential to increase throughput of analysis for quantitative shotgun proteomics experiments when compared to 2-plex and 4-plex methods. The technology was subsequently applied to a longitudinal study of cerebrospinal fluid proteins from subjects undergoing intravenous immunoglobulin treatment for Alzheimer’s disease. Results from this study identify a number of protein expression changes that occur in cerebrospinal fluid after 3 and 6 months of treatment compared to a baseline and compared to a drug washout period. A visualization tool was developed for this dataset and is presented. The tool can aid in the identification of key peptides and measurements. One conclusion aided by the visualization tool is that there are differences in considering peptide-based observations versus protein-based observations from quantitative shotgun proteomics studies.